The Debs centennial : written on the 100th anniversary of the birth of Eugene V. Debs - Cannon, James P. (New York : Pioneer Publishers, 1956)
Bibliotheek François Vercammen
Titel op kaft: Eugene V. Debs : the Socialist movement of his time - its meaning for today
Engels
Brochure